Molar incisor hypomineralization treatment with casein phosphopeptide and amorphous calcium phosphate in children - Pasini, Marco; Giuca, Maria R; Scatena, Martina; Gatto, Roberto; Caruso, Silvia (Minerva stomatologica, 2018)
The purpose of this study was to evaluate the sensitivity of teeth with MIH in children before and after the use of a tooth mousse containing casein phosphopeptide and amorphous calcium phosphate (CPP-ACP). Forty patients, both males and females, aged from 8 to 13 years old that had a molar with MIH hypersensitivity were included in this study. In the test group (20 subjects), a tooth mousse with CPP-ACP was used while fluoride toothpaste was used in the control group. Dental sensitivity to mechanical and thermal stimuli was evaluated before (T0) and 120 days after the beginning of the treatment (T1). In the test group, the thermal sensitivity decreased significantly (P<0.05) from T0 to T1 (2.4±0.6 to 1.1±0.4) while in the control group resulted very similar (from 2.3±0.5 to 2.2±0.4). Similarly, mechanical sensitivity decreased significantly (P<0.05) from 7.8±1 to 3.8±0.6 while in the control group decreased not significantly (from 7.5±1.3 to 7.2±0.8). No significant difference (P>0.05) was observed by comparing males with females. The use of the remineralizing agent containing CPP-ACP resulted in a significant improvement in dental sensitivity in patients with MIH.